The Influence of the Health Belief Model on Reproductive Health Behavior among Adolescents in Surakarta, Indonesia - Bita Lestari; Ika Sumiyarsi Sukamto; Okid Parama Astirin; Revi Gama Hatta Novika; Vitri Widyaningsih (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Adolescents are vulnerable to reproductive health problems. Globally, approximately 1.7 million adolescents are living with HIV, and 12 million births occur among those aged 15–19 years. In Surakarta, 224 cases have been reported, highlighting the need for a Health Belief Model (HBM)-based approach. This study aimed to analyze the influence of HBM constructs on adolescent reproductive health behavior in Surakarta, both directly and indirectly. Subject and method: This was a quantitative study with a cross-sectional design conducted among 200 respondents selected through multistage random sampling from five secondary schools. Data were collected using a structured questionnaire and analyzed using simple logistic regression and path analysis. Results: Bivariate analysis showed that perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy were significantly associated with reproductive health behavior (p < 0.05). In multivariate analysis, self-efficacy had a positive and significant effect (b = 0.08; p = 0.015), perceived barriers had a negative and significant effect (b = -0.03; p = 0.034), and cues to action had a positive and significant effect (b = 0.19; p < 0.001). In addition, several HBM components had indirect effects on reproductive health behavior through self-efficacy as a mediating variable. The model demonstrated a good fit to the data (p = 0.441; RMSEA = 0.000; CFI = 1.000; TLI = 1.003; SRMR = 0.016). Conclusion: The components of the Health Belief Model significantly influence adolescent reproductive health behavior, both directly and indirectly through self-efficacy. Reproductive health interventions should emphasize improving self-efficacy and strengthening behavioral enabling factors.